Lost and gone forever : a novel of Scotland Yard's Murder Squad - Grecian, Alex (Scotland Yard's Murder Squad, 2016)
"Many changes have happened to the Murder Squad. Rash actions have cost Sergeant Nevil Hammersmith his job, and in response he has set up his own private detective agency. Inspector Walter Day has been missing for a year, and no one knows where he is--though there is a strong suspicion that Saucy Jack has him. Hammersmith has made finding Day his primary case, and he has company--a pair of bounty hunters, a man and a woman. It is only gradually that he has come to realize that they are not what they seem"--